2016
DOI: 10.3390/ijms17071120
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Valvular Heart Diseases: Potential Role as Markers and Actors of Valvular and Cardiac Remodeling

Abstract: miRNAs are a class of over 5000 noncoding RNAs that regulate more than half of the protein-encoding genes by provoking their degradation or preventing their translation. miRNAs are key regulators of complex biological processes underlying several cardiovascular disorders, including left ventricular hypertrophy, ischemic heart disease, heart failure, hypertension and arrhythmias. Moreover, circulating miRNAs herald promise as biomarkers in acute myocardial infarction and heart failure. In this context, this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 73 publications
(90 reference statements)
0
42
0
Order By: Relevance
“…Matrix vesicles contribute to calcification by carrying and depositing calcium crystals [33]. MicroRNAs are roughly 22 nucleotides long, singlestranded molecules that function to regulate gene expression by binding to mRNA, usually in the 3'UTR, to decrease mRNA translation and stability [34], microRNAs have also been found to play an important role in cardiovascular diseases [35][36][37][38][39]. We have found high enrichment of microRNAs after 20 days of Lp (a) treatment in HAVICs.…”
Section: Discussionmentioning
confidence: 94%
“…Matrix vesicles contribute to calcification by carrying and depositing calcium crystals [33]. MicroRNAs are roughly 22 nucleotides long, singlestranded molecules that function to regulate gene expression by binding to mRNA, usually in the 3'UTR, to decrease mRNA translation and stability [34], microRNAs have also been found to play an important role in cardiovascular diseases [35][36][37][38][39]. We have found high enrichment of microRNAs after 20 days of Lp (a) treatment in HAVICs.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, it has been suggested that miRs could serve as potential diagnostic biomarkers for a multitude of pathologies in humans. Recent studies have revealed that aberrant miR expression profiles are associated with a variety of cardiovascular pathologies including hypertrophy, heart failure, arrhythmias and AMI (19,20). Indeed, increased circulating levels of several myomiRs (miRNA-1, -19, -133a, -133b) which are highly expressed in skeletal muscle, as well as in the heart, were recorded (21).…”
Section: Discussionmentioning
confidence: 99%
“…120 Circulating miRNA may be involved in critical biological processes underlying cardiovascular disorders and are currently being investigated as biomarkers in cardiovascular disease. 121 Examples of potential miRNA biomarkers in AS include miR-133a, which was shown to predict the extent of regression of LV hypertrophy after SAVR 122 ; miR-21, which was shown to be associated with LV fibrosis 123 ; and miR-210, which was independently associated with mortality in patients with moderate-to-severe AS. 124 miRNA research is expected to expand considerably in the coming years, and new candidate biomarkers will likely be identified.…”
Section: Markers Of Alteration In Cardiac Metabolismmentioning
confidence: 99%
“…124 miRNA research is expected to expand considerably in the coming years, and new candidate biomarkers will likely be identified. 121 …”
Section: Markers Of Alteration In Cardiac Metabolismmentioning
confidence: 99%